Embracing the witch and the goddess : feminist ritual-makers in New Zealand - Rountree, Kathryn (Routledge, 2004)
Embracing the Witch and the Goddess is detailed survey of present-day feminist witches. It examines the attraction of witchcraft for its practitioners, and explores witches' rituals, views and beliefs about how magic works.